E-040 Altmetrics and neuro-interventional surgery: what determines 'trending' in online media?. (4th August 2020) - Alotaibi, N; Harker, P; Robertson, F; Vranic, J; Koch, M; Stapleton, C; Leslie-Mazwi, T; Patel, A
Abstract : Background: Alternative metrics (Altmetrics) are increasingly being used as a new metric of scientific dissemination by most medical journals. The aim of this study is to investigate predictors of higher Altmetric scores within the neuro-interventional surgery scope. Methods: We performed a comprehensive search for neuro-interventional related publications using the Altmetric database. Articles were selected based on wide-range search criteria that include terms 'interventional', 'neuroradiology', 'neurosurgery' and 'neuro-intervention'. We studied all online references for any article mentioned on Facebook, Twitter, blogs, and mainstream media sources. The strength of associations between all metrics was studied using Pearson correlation coefficient. Values close to 1 indicates strong correlation. Results: A total of 12, 501 articles pertinent to neuro-intervention were obtained from the Altmetric database. These articles had an average of an altimetric score of 8 (95% CI for the mean 7.7 to 9.2). The strongest correlations for Altmetrics were for the following online mentions: general news outlets (Pearson's r: 0.89), Twitter (0.78), Facebook (0.48) and Reddit (0.45). Interestingly, Wikipedia, peer-reviewed outlets and LinkedIn mentions had the weakest correlations coefficients (0.11, 0.21, and 0.00, respectively). Journals with social media presence had the highest average of total altimetric scores compared to journals without social media accounts. Conclusions: Compared to general news outlets and Twitter, professional online networks such as peer-reviewed outlets and LinkedIn did not have a significant association with high altermetric 'trending' scores in neuro-interventional surgery. The long-term impact of these metrics on citations or funding requires a prospective analysis. Disclosures: N. Alotaibi: None. P. Harker: None. F. Robertson: None. J. Vranic: None. M. Koch: None. C. Stapleton: None. T. Leslie-Mazwi: None. A. Patel: None.